Pengembangan Sistem Pelacakan Proyek Berbasis Web dengan Rapid Application Development Berdasarkan Studi Kasus PT. XYZ - Maria Nila Anggia Rini; Agata Filiana; Laurentius Kuncoro Probo Saputra; Gabriel Indra Widi Tamtama; Joel Adhi Tanuwijaya; Lukas Kurniawan; Bastian Surya H (STMIK Budi Darma, 2022)
PT. XYZ is a company that supplies automotive spare parts with a complex business workflow. One project consists of several jobs involving a series of steps and different sections of the department. In this study, we developed a web-based project tracking system using rapid application development based on a set of user requirements. The system was tested using black box testing which indicated success in response to its functionality. The result successfully provided employees the means to select a job according to their order, upload files, write notes, and pass the job to the next section when done. For Inspection and Assembly, the testing showed success for returning jobs to Design when revisions were required. Assembly was also able to declare project completion when every job has been fully executed by its respective sections. Every stage of the project was successfully recorded which provided information on the progress of each project to the management. Furthermore, our testing also found the system to be capable of providing a facility for customer to track the progress and duration of their project anywhere and anytime by entering a project code.